p53 is linked directly to homologous recombination processes via RAD51/RecA protein interaction. - Stürzbecher, H W (1996)
The tumour suppressor p53 prevents tumour formation after DNA damage by halting cell cycle progression to allow DNA repair or by inducing apoptotic cell death. Loss of wild-type p53 function renders cells resistant to DNA damage-induced cell cycle arrest and ultimately leads to genomic instabilities including gene amplifications, translocations and aneuploidy. Some of these chromosomal lesions are based on mechanisms that involve recombinatorial events. Here we report that p53 physically interacts with key factors of homologous recombination: the human RAD51 protein and its prokaryotic homologue RecA. In vitro, wild-type p53 inhibits defined biochemical activities of RecA protein, such as three-way DNA strand exchange and single strand DNA-dependent ATPase activity. In vivo, temperature-sensitive p53 forms complexes with RAD51 only in wild-type but not in mutant conformation. These observations suggest that functional wild-type p53 may select directly the appropriate pathway for DNA repair and control the extent and timing of the production of genetic variation via homologous recombination. Gene amplification an other types of chromosome rearrangements involved in tumour progression might occur not only as result of inappropriate cell proliferation but as a direct consequence of a defect in p53-mediated control of homologous recombination processes due to mutations in the p53 gene.